Does Local Financial Development Matter for Firm Lifecycle in India? - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank Group, Washington, DC, 2014)
The differences in financial development across Indian states, while seeming substantial, have a minor effect on firm lifecycle and growth. These results hold controlling for differences in labor regulations across states, capital intensity, and for firms born before and after the major reforms. There is no evidence that firms in financially dependent industries have different lifecycle profiles or grow faster in financially developed states than underdeveloped states. Overall, firms in the formal manufacturing sector grow as they age whereas in the informal sector, firms have a declining lifecycle, but in both cases little evidence is found that financial institutions matter for firm lifecycle. The findings of this paper suggest that size and depth differences in financial development across Indian states are likely dwarfed by overall inefficiencies that characterize state-dominated financial systems, with important implications for the reforms of the Indian financial system going forward.